2017
DOI: 10.3390/ijerph14060557
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neighbourhoods and the Social Environment on Sedentary Behaviour in Older Adults in Three Prospective Cohorts

Abstract: Sedentary behaviour is an emerging risk factor for poor health. This study aimed to identify ecological determinants of sedentary behaviour, for which evidence is currently scarce. The study participants were community dwelling adults from, respectively, the Lothian Birth Cohort 1936 (n = 271, mean age 79) and the 1930s (n = 119, mean age 83) and 1950s (n = 310, mean age 64) cohorts of the West of Scotland Twenty-07 study. The outcome measure, percentage of waking time spent sedentary (sedentary time), was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 59 publications
0
24
1
Order By: Relevance
“…A study which aimed to identify ecological determinants of sedentary behaviour, and included LBC1936 data, found that being in a carer role was related to lower levels of sedentary behaviour, and increased sedentary behaviour was related to a fear of crime and perceived absence of neighbourhood services 20 . Greater social disadvantage measured using a range of socioeconomic position measures has also been associated with increased time spent sedentary among retired individuals 21 .…”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“…A study which aimed to identify ecological determinants of sedentary behaviour, and included LBC1936 data, found that being in a carer role was related to lower levels of sedentary behaviour, and increased sedentary behaviour was related to a fear of crime and perceived absence of neighbourhood services 20 . Greater social disadvantage measured using a range of socioeconomic position measures has also been associated with increased time spent sedentary among retired individuals 21 .…”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“…Social capital is also "a propensity of people in a society to cooperate to produce socially efficient outcomes" and includes "the norms of reciprocity and trustworthiness" that arise from connections among individuals [20]. The concept of social capital is also widely used in economics, finance, and other social sciences [21][22][23][24][25]. Researchers, including those focused on the development of rural economics, subdivide social capital into measurable components.…”
Section: The Effect Of Two Kinds Of Social Capital On Farm Household'mentioning
confidence: 99%
“…The determinants and consequences of sedentary behavior are gaining recognition as an independent risk factor. In addition, neighborhood environmental factors associated with sedentary behavior among retirees using objective measures can help guide interventions [ 12 ]. Methodological advances in conducting street audits are helpful to identify the impact of different microscale environmental features on walking patterns among older adults [ 13 , 14 ].…”
Section: Editorialmentioning
confidence: 99%